Further material of the ceratosaurian dinosaur Syntarsus from the Elliot Formation (Early Jurassic) of South Africa - Munyikwa, Darlington (Bernard Price Institute for Palaeontological Research, 1999)
Two further fossils recovered from the Elliot Formation in South Africa are referred to the ceratosaurian genus Syntarsus: a partial pelvis and a well preserved and articulated snout. The pelvic fragment consists of most of the posterior end of the left ilium and sacrum, with a small part of the right ilium attached. The acetabular area and ‘brevis shelf’ of the left ilium are well preserved, as is the ventral surface of the sacrum. These parts show features characteristic of Syntarsus material from Zimbabwe. The snout has the premaxillae, maxillae, nasals and dentaries from both sides preserved, of which only the premaxillae are more or less complete. The premaxilla has four alveoli and the maxilla nine, and the maxilla bears the characteristic dimpling on its lateral surface also seen in Syntarsus material collected in Zimbabwe. The snout also possesses the characteristic small diastema or subnarial gap between the premaxillary and maxillary teeth shown by Syntarsus material from elsewhere. The snout is strongly compressed bilaterally and the jaws are tightly closed, so that the dentary teeth are obscured beneath the upper dentition. This compression has crushed the palatal region, obscuring palatal details.
Keywords: Dinosauria; Theropoda; Elliot Formation; Jurassic; Stormberg